Schistura (Teleostei: Nemacheilidae) in the Mae Khlong basin in southwestern Thailand with description of a new species - Page, Lawrence M.; Plongsesthee, Rungthip; Beamish, F. William H.; Kangrang, Punnatut; Randall, Zachary S.; Singer, Randal A.; Martin, Zachary P. (Zootaxa, 2012)
Recent fieldwork has revealed the presence of six species of Schistura McClelland 1838 in the Mae Khlong basin in south-western Thailand. These include S. sexcauda (Fowler 1937), S. balteata (Rendahl 1948), S. mahnerti Kottelat 1990, therecently described S. aurantiaca Plongsesthee et al. 2011 and S. tenebrosa Kangrang et al. 2012, and a newly discoveredspecies described herein. Schistura sexcauda previously was the only Schistura species known in the Mae Khlong, andit was mis-identified as S. desmotes (Fowler 1934). Schistura pantherina, n. sp., is easily distinguished from all other species of Schistura by its distinctive color pattern. It appears to be endemic to the Mae Nam Kwai Noi system.